Pengaruh Penerapan Media Video Interaktif Berbasis Edpuzzle Pada Mata Pelajaran Pendidikan Pancasila Terhadap Minat Belajar Peserta Didik Kelas VIII SMPI Fatahilah Kediri - Laila Puspitasari; Listyaningsih (Universitas Negeri Surabaya (Unesa), 2026)
Grade VIII students of SMPI Fatahilah have different learning interests where students who have a high interest in learning have a tendency to be diligent and enthusiastic in learning, as well as students who have a low interest in learning tend to be lazy. This causes teachers to innovate in teaching and learning activities by applying interactive video media to attract students' enthusiasm to be more interested in learning. The purpose of this study is to test the effect of the application of edpuzzle-based interactive video media in Pancasila Education subjects on the learning interest of grade VIII students at SMPI Fatahilah. This research is a quantitative research with a quasi experiment method. The population in this study is all students of grade VIII of SMPI Fatahilah where class VIII A is as an experimental class and class VIII B is a control class with a total of 20 students in each class. Data analysis used non-parametic statistics of the mann whitney test. The results of the study were -1.5 < 127 at a significance level of 0.05, then H0 was rejected and Ha was accepted, this shows the influence of the application of edpuzzle-based interactive video media compared to Power Point media as a comparative medium to determine the influence of edpuzzle-based interactive video media on the learning interest of grade VIII students of SMPI Fatahilah. The results of this study are relevant to Vgotsky's theory which emphasizes social interaction through discussion, exchange of opinions and giving input, which fosters knowledge that can be assisted by intermediary tools, namely interactive video media based on edpuzzles in the process of interaction during learning. Keywords : Edpuzzle. Interest in Learning, Interactive Video